2018
DOI: 10.1111/jop.12715
|View full text |Cite
|
Sign up to set email alerts
|

Expression of endoplasmic reticulum stress protein in rabbit condyle cartilage following anterior disk displacement

Abstract: These results indicate that the ER stress pathway is activated in ADD cartilage and might promote the development of TMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In previous studies, we reported that ER stress pathway played an essential role in the process of apoptosis induced by excessive hydrostatic pressure on chondrocytes in the mandibular condyle (Xu et al, 2017). We also found that ER stress pathway might be involved in the development of ADD by promoting chondrocyte apoptosis (Xu et al, 2018). The conclusions drawn from our studies are consistent with previous research showing that aberrant mechanical stress leads to cartilage degeneration by triggering ER stress-mediated apoptosis in the TMJ (Li et al, 2013;Yang et al, 2020).…”
supporting
confidence: 91%
“…In previous studies, we reported that ER stress pathway played an essential role in the process of apoptosis induced by excessive hydrostatic pressure on chondrocytes in the mandibular condyle (Xu et al, 2017). We also found that ER stress pathway might be involved in the development of ADD by promoting chondrocyte apoptosis (Xu et al, 2018). The conclusions drawn from our studies are consistent with previous research showing that aberrant mechanical stress leads to cartilage degeneration by triggering ER stress-mediated apoptosis in the TMJ (Li et al, 2013;Yang et al, 2020).…”
supporting
confidence: 91%
“…It can cause structural damage and abnormal articular forces to induce OA-like lesions directly by using surgical and mechanical devices. The common surgical methods include discectomy ( Hinton, 1992 ; Lan et al, 2017 ; Liu X. et al, 2020 ; Saito et al, 2021 ), partial discectomy ( Man et al, 2009 ; Xu et al, 2009 ; Lei et al, 2022 ), disc perforation ( Embree et al, 2015 ; Luo et al, 2020 ; Ruscitto et al, 2020 ), anterior disc displacement ( Togni et al, 2018 ; Xu et al, 2018 ; Nguyen et al, 2020 ), injury of the condylar surface ( Ishimaru and Goss, 1992 ; Wang F. et al, 2017 ), and postero-superior displacement of the mandible ( Imai et al, 2001 ; Liu et al, 2006 ) ( Table 3 ). These six methods well mimic advanced symptoms of joint injury in clinical patients, but they are not starting factors in general TMJOA.…”
Section: Classification Of Animal Models In Temporomandibular Joint O...mentioning
confidence: 99%
“…Mice, rats, rabbits, pigs, and sheep are widely used in vivo preclinical studies as surgical induction models. Rabbits are the most used models ( Imai et al, 2001 ; Man et al, 2009 ; Embree et al, 2015 ; Xu et al, 2018 ; Saito et al, 2021 ), because they are quite large and strong enough to fight off infection. Therefore, they tolerate surgeries; their joint tissues are large enough to undergo surgery and wear mechanical devices.…”
Section: Classification Of Animal Models In Temporomandibular Joint O...mentioning
confidence: 99%
“…Anterior disc displacement (ADD) is commonly associated with the beginning of TMD and then it has been regarded as a common surgical model for TMD in animals. Xu et al 70 utilized adult rabbits to surgically induce ADD. Specifically, a 3 cm incision was made along the right zygomatic arch, and the zygomatic‐squamosal suture was exposed in the anesthetized rabbit.…”
Section: Animal Models Of Tmdmentioning
confidence: 99%